But the Scores Don't Show How I Really Function: A Feedback Method to Reveal Cognitive Distortions Regarding Normal Neuropsychological Test Performance. Issue 2 (4th March 2017) - Carone, Dominic A.
ABSTRACT: Neuropsychologists commonly provide feedback to patients with a high degree of cognitive complaints in the context of normal neuropsychological test performance. Patients are sometimes not reassured by this feedback because they blame external factors (e.g., the tests are wrong) and do not develop insight about internal factors (e.g., distorted self-perception) that could lead to better understanding about why high symptom reporting is present in the context of normal test results. This article presents the first formal feedback model for neuropsychologists to use with such patients that helps reveal the presence of cognitive distortions that result in high cognitive complaints. The critical elements of this model incorporate self-ratings of neuropsychological test performance, comparing those ratings to actual test performance, and presenting discrepancies to patients in an objective, professional, and respectful manner. Ways in which this feedback model may lead to improved patient outcomes and reductions in healthcare costs are discussed.